Pengaruh Kepemimpinan Terhadap Kinerja Karyawan - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Leadership is one of the factors that shape and help others to enthusiastically work and achieve the planned object in relation to the success of the organization realize the objectives are largely determined by the high performance leadership and employed in carrying out their duties. Problems that exist in the company are leaders in their duty to behave authoritarian that provide employment to its employees at will without doing approaches that can stimulate employees to work well so that the performance of the employees to be ineffective. This research was conducted on employees financing (leasing) in the Medan city. The purpose of the study is to determine the effect of leadership on performance. The sampling technique is done with nonprobability sampling technique sampling technique accidental or coincidental samples, where anyone who by chance met with investigator. Based on that the researchers took a sample of 54 people. The technique of collecting data using questionnaires, ie by making a list of questions in the form of a questionnaire addressed to the employees. Data where analyzed using correlation test, t test and determination. The result using the t test can be concluded that the leadership (x) significantly affects performance (y) at the significance level of 0.05. simple correlation coefficient values between the leadership and the leadership of the obtained performance Rx1x2y = 0.717, meaning the influence of employee performance is stronger of leadership to be around the interval from 0.80 to 1.00. R-square value obtained amounted to 0.514 indicate that about 51.4% Y variables (employee performance) can be explained by the leadership variable (x). of practically it can be said that the contribution of leadership (X) to variable Y (the performance of employees) is 51,4%, the rest (100%-51,4%-48,6%) is influenced by other variables.